PENGARUH LABELISASI HALAL, HARGA PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN IMPOR DI KALANGAN MAHASISWA (Studi Empiris pada mahasiswa Universitas Islam Malang Fakultas Ekonomi dan Bisnis Angkatan 2018) - Putri Ningsih; Nur Diana; M Cholid Mawardi (Universitas Islam Malang, 2022)
This study aims to examine whether simultaneously and partially the variables of halal labeling,product prices, and product quality on purchasing decisions of imported food products. This studyuses a quantitative method by distributing questionnaires using a google form via online. Thisstudy took a sample of students from the Islamic University of Malang, the Faculty of Economicsand Business, batch 2018. The results obtained from this study are that the halal labeling variables,product prices, and product quality have a significant effect on purchasing decisions. Partiallyhalal labeling has a significant effect on purchasing decisions, partially product prices have asignificant effect on purchasing decisions, and partially product quality has a significant positiveeffect on purchasing decisions.